Effects of waterlogging stress on plant-pathogen interaction between Fusarium poae and wheat/ barley - Martinez, Mauro; Arata, Agustín Francisco; Lázaro, Laura; Stenglein, Sebastian Alberto; Dinolfo, María Inés (Acta Scientiarum. Agronomy, 2019)
Waterlogging stress is one of the abiotic factors which causes damage to crops affecting yield components and grain quality of wheat and barley. On the other hand, Fusarium poae is one of the most common Fusarium species isolated from wheat and barley. The aim of this study was to evaluate the effects of waterlogging and F. poae on disease parameters, yield components and grain quality of durum and bread wheat and barley. The experiment was carried out using pots under greenhouse conditions. Four treatments were applied: control/control (W0F0), control/F. poae (W0F1), waterlogging/control (W1F0) and waterlogging/F. poae (W1F1). The results showed that incidence, severity and FHB index of F. poae were higher in W0F1 compared to W1F1 suggesting that waterlogging treatment would be generating no favorable conditions for fungal growth. Therefore, yield components and grain composition and quality were significantly affected by the Fusarium presence and waterlogging treatment which could induce changes in parameters mainly related to the industrial quality of wheat and barley. These results highlight the behavior of wheat and barley under the combination of abiotic and biotic stress.